2021
DOI: 10.48550/arxiv.2108.04266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Search for Low $W_0$

Igor Broeckel,
Michele Cicoli,
Anshuman Maharana
et al.

Abstract: The magnitude of the vacuum expectation value of the Gukov-Vafa-Witten superpotential |W 0 | plays a central role in the phenomenology of type IIB flux compactifications. Recent analytical constructions have shown that perturbatively flat vacua can be used to obtain very low values of |W 0 |. We present systematic algorithms to carry out exhaustive numerical searches for such vacua. We also analyse them in the statistical context, as part of the entire ensemble of type IIB flux vacua at low |W 0 |. Our prelimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 69 publications
1
25
0
Order By: Relevance
“…In the large voume regime the N = 2 special geometry data is encapsulated in the prepotential 11226 [12] taken from [15]. The shown distances are the ones computed in said paper.…”
Section: )mentioning
confidence: 93%
See 3 more Smart Citations
“…In the large voume regime the N = 2 special geometry data is encapsulated in the prepotential 11226 [12] taken from [15]. The shown distances are the ones computed in said paper.…”
Section: )mentioning
confidence: 93%
“…2.1 P 4 1,1,2,2,6 [12] The topological numbers corresponding to the P 4 1,1,2,2,6 [12] hypersurface and appearing in its prepotential are given by…”
Section: Abovementioning
confidence: 99%
See 2 more Smart Citations
“…For the recent debate on Swampland conjectures see for example [1][2][3] and related reviews [4][5][6]. Also, an incomplete list of 10d supergravity dS solutions and other related issues is [7][8][9][10][11][12] 4 For recent developments on related work see [15][16][17][18][19][20][21] the cosmological inflation have been studied. It was found that hybrid inflation is successfully implemented with the internal volume modulus acting as the inflaton [28], and the rôle of the waterfall field is played by open string excitations associated with the D7 brane stacks [29].…”
Section: Introductionmentioning
confidence: 99%